Atomic imprinting into metallic glasses. Issue 1 (December 2018) - Li, Rui; Chen, Zheng; Datye, Amit; Simon, Georg; Ketkaew, Jittisa; Kinser, Emily; Liu, Ze; Zhou, Chao; Dagdeviren, Omur; Sohn, Sungwoo; Singer, Jonathan; Osuji, Chinedum; et al.
Abstract Nanoimprinting by thermoplastic forming has attracted significant attention due to its promise of low-cost fabrication of functionalized surfaces and nanostructured devices, and metallic glasses have been identified as a material class ideally suited for nanoimprinting. In particular, their featureless atomic structure suggests that there may not be an intrinsic size limit to the material's ability to replicate a mould. Here we demonstrate atomic-scale imprinting into a platinum-based metallic glass alloy under ambient conditions using atomic step edges of a strontium titanate single crystal as a mould. The moulded metallic glass replicates the 'atomic smoothness' of the strontium titanate, with identical roughness to the one measured on the mould even after multiple usages and with replicas exhibiting an exceptional long-term stability of years. By providing a practical, reusable, and potentially high-throughput approach for atomic imprinting, our findings may open novel applications in surface functionalization through topographical structuring. Nanoimprinting is a technique where the surface features of a mould can be transferred onto a replica and is relevant to the production of nanostructured devices. The authors report a method that enables the imprinting of structural features of SrTiO3 single crystals at the atomic level into a replica made from bulk metallic glass.